2015
DOI: 10.1371/journal.pmed.1001778
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraception and the Risk of HIV Acquisition: An Individual Participant Data Meta-analysis

Abstract: In a meta-analysis of individual participant data, Charles Morrison and colleagues explore the association between hormonal contraception use and risk of HIV infection in sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
220
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(228 citation statements)
references
References 72 publications
(140 reference statements)
7
220
1
Order By: Relevance
“…Recently, a study on hormonal contraception and HIV acquisition reports individual patient data of several studies. Meta-analysis indicates that DMPA may increase HIV acquisition (controlling confounders and adjusted odds ratio of 1.5) compared with other methods of contraception (Morrison et al 2015). In vitro studies on hormone effects support the clinical studies discussed earlier.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Recently, a study on hormonal contraception and HIV acquisition reports individual patient data of several studies. Meta-analysis indicates that DMPA may increase HIV acquisition (controlling confounders and adjusted odds ratio of 1.5) compared with other methods of contraception (Morrison et al 2015). In vitro studies on hormone effects support the clinical studies discussed earlier.…”
Section: Introductionsupporting
confidence: 52%
“…The use of contraceptive pills by HIV-1-seropositive women is considered to be important for preventing unintended pregnancies and reducing mother-to-child transmissions. Although these hormones help to prevent unintended pregnancies, they also enhance HIV-1 acquisition (Ramjee & Wand 2012, Morrison et al 2015. Several epidemiological reports are inconsistent for progesterone-containing contraceptive use and risk of HIV-1 acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Although controversial, a meta-analysis of observational studies in sub-Saharan Africa has suggested that DMPA may be associated with increased HIV risk, particularly in younger women. [14] Although more evidence is needed to empirically confirm this association, women who may be at risk for HIV should be counselled to also use condoms if they insist on using DMPA for contraception.…”
Section: Prevention Of Unintended and Unwanted Pregnanciesmentioning
confidence: 99%
“…Understanding biological contributors to HIV risk in women is therefore important for public health. Although still a topic of great debate there is a growing body of evidence that both endogenous and exogenous ovarian hormones, including estradiol and progesterone, are associated with increased HIV acquisition in women (3)(4)(5)(6)(7). Studies of nonhuman primates have shown that SHIV infection occurs more frequently during the progesteronedominant luteal phase of the menstrual cycle (8,9), and recent in vitro explant cultures of human cervical tissue have also shown that HIV infects explants collected during the luteal phase more productively than those collected during the follicular phase (10).…”
mentioning
confidence: 99%
“…Studies of nonhuman primates have shown that SHIV infection occurs more frequently during the progesteronedominant luteal phase of the menstrual cycle (8,9), and recent in vitro explant cultures of human cervical tissue have also shown that HIV infects explants collected during the luteal phase more productively than those collected during the follicular phase (10). Furthermore, progestins, which are synthetic progesterone derivatives commonly used in injectable hormonal contraceptives, have been shown to increase HIV acquisition risk by as much as 1.5-to 2.0-fold based on the latest meta-analysis (7,11). Clearly, these results indicate a link between ovarian hormones and HIV risk, and understanding the mechanisms underpinning these observations may have important implications for sexual and reproductive health.…”
mentioning
confidence: 99%